Profile of High Order Thingking Skill (HOTS) of Junior High School Students’ Grade 8 in Solving Linear Equation System Problems Based on Kinesthetic and Visual Learning Styles - Winda Syam Tonra; Mega Teguh Budiarto; Masriyah Masriyah; Wilda Syam Tonra (SAINTIS Publishing, 2019)
This qualitative research aims to describe profile high order thinking skill (HOTS) of Junior high school students’ grade 8 in solving linear equation system problems based on kinesthetic and visual learning styles. In collecting data, mathematics ability test and learning style questionnaire aims to select students to be research subjects. Then, problem solving tests to determine the high order thinking skills and interviews were used to obtain data on students' high order thinking skills that were not obtained from problem solving tests. There are 3 (three) aspects of HOTS in this study which are analyzing, evaluating and creating. The results of the study show that in the aspect of analyzing, students with kinesthetic and visual learning styles can distinguish the information needed, know what is sought and know the relationship between information. In creating aspect, kinesthetic and visual aspects can know ideas, strategies used and can implement these ideas and strategies in solving problems. Whereas in the Evaluation aspect, kinesthetic uses a strategy in checking the truth in the answer but the visual does not use the strategy. Thus, it can be concluded that the differences of kinesthetic students and visual students lay on strategies used in checking the truth of the answers of the problem given.